EFEKTIFITAS TERAPI PIJAT REFLEKSI KAKI UNTUK MENURUNKAN STRES PSIKOLOGIS PASIEN YANG DIRAWAT DI INTENSIF - Chanif -; Mariyam - (Universitas Muhammadiyah Semarang, 2015)
Intensif care unit are used by patients undergoing treatment program critical to get healing. The most of them experience psychological stress, both physical and psychological stress. This study aimed to compare the psychological stress in the experimental group before and after foot reflexology massage therapy using the control group. This study using quasi-experimental design using control group. Twenty critically ill patients undergoing intensive treatment chosen as sample. Sample criteria include adult conscious patients, males aged 18-60 years with and can communicate verbally. Data collection used instrument Depression Anxiety Stress Scale 42 (DASS 42) from Lovibond and Lovibond (1995). Results Matched-Pair Wilcoxon Signed Rank Test p value = 0:05, it means that there are differences in psychological stress scores in the treatment group after getting a foot reflexology massage therapy treatment for 30 minutes. Mann-Whitney test results obtained value of p = 0.317, it means that there are no significant differences in psychological stress scores between the experimental group and the control group. The existence of psychological stress that is not get attention and appropriate treatment, will have an impact on the longer treatment time, higher maintenance costs and loss of productivity of patients. It will also worsen the general condition of the patient. So that it requires the existence of stress management for critically ill patients who are undergoing treatment in the intensive care. Foot reflexology massage therapy became one of the alternatives that can be applied directly to the patient that does not cause adverse impact compared to using drugs.Keywords: foot reflexology, stress psychologic, intensive care.